On Students’ Willingness to Use Online Learning: A Privacy Calculus Theory Approach - Jiang, Xinyu; Goh, Tiong-Thye; Liu, Mengjun (Frontiers in Psychology, 2022)
Online learning platforms frequently collect and store learners' data to personalize content and improve learning analytics, but this also increases the likelihood of privacy breaches which may reduce learners' willingness to use online learning. This study aims to examine how perceptions of benefits, privacy, risk, and trust affect students' willingness to use online learning. We used the Privacy Calculus Theory as a theoretical framework for this study. To test the model, we surveyed 203 undergraduate students who used online learning. The results of the AMOS analysis revealed that students' risk perception has a significant negative effect on their willingness to use online learning, while their benefit perception and trust perception have positive effects. Furthermore, the study found that improved trust can reduce perceived risk and improve willingness to use online learning. Interestingly, privacy perception is not a significant predictor of students' willingness to use online learning, although it is a high concern factor. Implications, limitations, and future work are discussed at the end.